A Theoretical Need for Applying Flipped Learning to STEAM Education - Young Kyung Jung; Hyeonmi Hong (Halla Newcastle Education and Research Center, 2020)
This paper addresses the current problems of STEAM education and suggests a solution to solve one of the problems through adopting a method from Flipped Learning. Through the meticulous literature review, comparison, and analysis on STEAM and Flipped Learning, it will be shown that the methodology of Flipped Learning complements the weaknesses in STEAM. The conclusion is that since there is a theoretical need for applying Flipped Learning to STEAM, further research needs to be carried out to apply flipped learning in STEAM classes.